Plastic Root System Development Responses to Drought- Enhanced Nitrogen Uptake during Progressive Soil Drying Conditions in Rice - Suralta, Roel R. (2010)
In order to study the functional roles of plastic root system development (RSD) responses of rice to drought in terms of uptake of fertilizer nitrogen (N) applied prior to the onset of progressive drought, a root box experiment was conducted in a greenhouse. Two genotypes - drought-susceptible IR64 and drought-resistant strain DRS111 - were grown under two water conditions (continuously waterlogged, CWL, as control and droughted, DR) and two N treatments (without N, as control and with N at 120 kg ha-1). For the treatment with N fertilizer, half of the N rate was applied at basal prior to sowing while the remaining half was applied a day before withholding water for the DR treatment. Results showed that under progressive DR condition, plant growth, photosynthesis, transpiration, water use and relative chlorophyll content as indicated by soil and plant analysis development (SPAD) value were significantly higher with N applied during the onset of drought than without N in DRS111 only. This result was due to the greater ability of DRS111 than IR64 for plastic RSD through more initiation of L-type lateral root (LR) under progressive DR regardless of N treatment. Plastic RSD, in response to drought through greater promotion of L-type LR, can enhance not only the uptake of water but also of N if fertilizer N is applied during the onset of progressive drought stress in rice.
Keywords: Rainfed lowland rice